PENGARUH HEALTH EDUCATION TERHADAP PENGETAHUAN DAN SIKAP TENTANG DIET RENDAH GARAM PADA PASIEN HIPERTENSI - Halawa, Astuti; Usman, Andi Mayasari; Nursasmita, Rizqi (Universitas Nasional, 2023)
AbstractHypertension or better known as high blood pressure is a condition where a person's bloodpressure is above the normal or optimal limit, namely 120 mmHg systolic and 80 mmHgdiastolic. This study aims to determine the effect of health education on knowledge andattitudes about a low-salt diet in hypertensive patients at X Hospital in Central Jakarta.Quantitative research using a Quasi-Experiment approach with One Group Pre-test - Posttest. The sample in this study was 41 people from a population of 45 people. The sampletechnique was a purposive sampling. The research instrument used a questionnaire. Thestatistical test used was the Wilcoxon signed rank test to determine the difference betweenthe independent variables and the dependent variable. The research conducted on 41respondents showed that most of the characteristics of the respondents were female(73.20%), the minimum age was 25 years and the maximum age was 83 years, undergraduateeducation (36.60%), the respondents' knowledge before and after giving health educationabout a low-salt diet (p value 0.000), and the attitude of respondents before and after givinghealth education about a low-salt diet (p value 0.000). Two-variable research shows thatthere are differences in health education on knowledge and attitudes about low-salt diets inhypertensive patients. Keywords: health education, hypertension, diet for hypertension, low sodium dietAbstrakHipertensi adalah suatu keadaan dimana tekanan darah seseorang lebih tinggi dari batas idealatau normal, yaitu tekanan darah sistolik sebesar 120 mmHg dan tekanan darah diastoliksebesar 80 mmHg. Penelitian ini bertujuan untuk mengetahui pengaruh health educationterhadap pengetahuan dan sikap tentang diet rendah garam pada pasien hipertensi di RumahSakit X di Jakarta Pusat. Penelitian kuantitatif menggunakan pendekatan Quasi-Experimentdengan One Group Pre-test - Post-test. Sampel dalam penelitian ini berjumlah 41 orang daripopulasi 45 orang. Teknik sampel yang digunakan purposive sampling. Instrumen penelitianini menggunakan kuesioner. Uji statistik yang digunakan uji Wilcoxon signed rank test. Hasilpenelitian menunjukkan bahwa terdapat pengaruh antara perempuan (73,20%), minimal usiaadalah 25 tahun dan usia maksimal adalah 83 tahun, pendidikan sarjana (36,60%),pengetahuan responden sebelum dan sesudah pemberian health education tentang diet rendahgaram (p value 0,000), dan sikap responden sebelum dan sesudah pemberian healtheducation tentang diet rendah garam (p value 0,000). Kata kunci: pendidikan kesehatan, hipertensi, diet hipertensi, diet rendah garam